(untitled) (Research, Society and Development, 2020)
A few years ago, concerns about the need to recover degraded areas and to restructure the landscape began. One of the difficulties to produce native seedlings, among several factors, is the dormancy of the seeds of some species because even in favorable environments the seeds do not germinate. The objective of this study was to evaluate the influence of different methods of overcoming dormancy in the emergence of two species of the Fabaceae family, native to the Cerrado of the northeast of Mato Grosso do Sul, Brazil. Seven treatments were used for both species, where there was a combination of scarification with immersion in water. The dormancy break methods applied to interfere with the germination percentage and the emergence velocity index for both species. To Dimorphandra mollis, the best treatment is a scarification opposite to the hilum followed by immersion in water for 9 hours. To Hymenaea stigonocarpa, the use of at least two scarifications followed by immersion in water favors the percentage of germinated seeds while, two lateral scarifications to the hilum, combined with immersion in water, favors the velocity of the emergence of these seeds.